GENETICALLY MODIFIED FOODS PERCEPTION OF CONSUMERS IN THE GLOBALIZING WORLD: A CASE STUDY FROM TURKEY - Deniz SARICA; Dilara DURUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study was conducted by estimating logistic regression analysis to understand the factors affecting consumers’ perception and purchasing intention of genetically modified (GM) foods in Isparta, Turkey. The information was gathered through face-to-face interviews with 264 consumers in the city of Isparta, Turkey. It was determined that being younger and having a higher education level positively affect the purchase intention of GM foods. Also, trust in health and safety is a sufficient factor to increase purchase intention even if there is distrust of the government. However, perceived risks do not significantly affect consumers’ intentions to buy, and thus, benefit perception is more effective than risk perception. Consequently, the consumers’ attitudes determine their purchase intentions for GM foods. This research has practical implications for food industry policymakers and producers, who might devise methods to enhance consumer expenditure on GM foods based on their excellent taste and favorable contribution to a healthy diet. This will be valuable for doing consumer-oriented evaluations and product development to understand better and predict consumer reactions and behavior.